1988
DOI: 10.1677/joe.0.1180317
|View full text |Cite
|
Sign up to set email alerts
|

Major secretory protein of human decidualized endometrium in pregnancy is an insulin-like growth factor-binding protein

Abstract: Pregnancy-associated endometrial alpha 1-globulin (alpha 1-PEG) is quantitatively the major secretory protein product, synthesized and secreted in vitro, of the human decidualized endometrium during pregnancy. This protein has been purified from cytosolic extracts of this tissue and has now been characterized as a 32 kDa somatomedin/insulin-like growth factor (IGF)-binding protein. Immunoreactive alpha 1-PEG isolated from amniotic fluid exhibited identical physiochemical properties and IGF-I-binding characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…The strongly elevated IGF-BP1 levels confirm the reports from Iino et al [24] and Giudice et al [17], but are in disagreement not only with Lewitt et al [33] who found reduced serum protein levels, but at first sight also with the demonstration of decreased mRNA levels in the decidua, which is the first location of IGF-BP1 production in pregnancy [6,25] of pre-eclamptic patients [18]. The combined information deriving from this pattern of increased protein levels in pre-eclampsia, reduced decidual mRNA synthesis together with reduced serum levels in the second trimester of later pre-eclamptic pregnancies [2,16,19,22] may thus favour the hypothesis of an increased hepatic production in late pregnancy [18] or shortly before the symptoms would appear.…”
Section: Cross-sectional Studysupporting
confidence: 55%
“…The strongly elevated IGF-BP1 levels confirm the reports from Iino et al [24] and Giudice et al [17], but are in disagreement not only with Lewitt et al [33] who found reduced serum protein levels, but at first sight also with the demonstration of decreased mRNA levels in the decidua, which is the first location of IGF-BP1 production in pregnancy [6,25] of pre-eclamptic patients [18]. The combined information deriving from this pattern of increased protein levels in pre-eclampsia, reduced decidual mRNA synthesis together with reduced serum levels in the second trimester of later pre-eclamptic pregnancies [2,16,19,22] may thus favour the hypothesis of an increased hepatic production in late pregnancy [18] or shortly before the symptoms would appear.…”
Section: Cross-sectional Studysupporting
confidence: 55%
“…The expression of IGFBP-1 mRNA and protein in endometrial epithelial and stromal cells [24][25][26][27][28][29][30], and of immunoreactive pregnancy-associated endometrial al-globulin (PEG) in endometrial tissue during the menstrual cycle and in decidual cells throughout pregnancy [32] has been demonstrated. IGFBP-1 is first detected during the mid-secretory phase (Days 19-23), with the highest intensity associated with stromal cells during the late luteal phase in humans and baboons [31][32][33][34]; not all the endometrial tissues were found to be immunostained for al-PEG [32].…”
Section: Discussionmentioning
confidence: 99%
“…Six distinct forms of IGFBPs have been identified and are synthesized and secreted by a variety of cell types [23]. In the uterus, the expression of mRNA and protein for IGFBP-1 has been demonstrated and immunohistochemically localized in human endometrial epithelial and stromal cells during the late luteal phase of the menstrual cycle, in human decidual cells during early pregnancy, and in baboon decidual cells throughout pregnancy [24][25][26][27][28][29][30][31][32][33][34]. Relaxin and progesterone (P 4 ) have been shown to stimulate IGFBP-1 production in stromal cells and endometrial explant culture [24,35].…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 , though not necessary for decidualization, is a potent enhancer of decidualization [8]. Decidualization of the endometrial stromal cells was determined by several criteria including morphology and expression of prolactin (PRL) and insulin-like growth factor binding protein-1 (IGFBP-1), both of which are specific markers of decidualized stromal cells [9,10]. In addition, we have examined the effect of decidualization on IL-IP1 expression in an enriched fraction of endometrial stromal cells.…”
Section: Introductionmentioning
confidence: 99%